2012
DOI: 10.3109/17518423.2012.707693
|View full text |Cite
|
Sign up to set email alerts
|

Self-regulated music stimulation for persons with Alzheimer's disease: Impact assessment and social validation

Abstract: An active music stimulation condition can be viable, effective, and socially preferable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 58 publications
0
12
0
Order By: Relevance
“…The number of participants varied considerably across studies, with a median sample size of 11 (range 3-77). Nine studies were defined as high quality (Avondino & Antoine, 2016;Beach et al, 2015;Conde-Sala et al, 2013Magai et al, 1996, P€ oll€ anen & Hirsim€ aki, 2014Starkstein, Jorge, Mizrahi, & Robinson, 2006;Swall, Ebbeskog, Lundh, & Fagerberg, 2015), seven as moderate quality (Asplund, Jansson, & Norberg, 1995;Asplund, Norberg, Adolfsson, & Waxman, 1991;Biringer, Anderson, & Strubel, 1988;Biringer & Anderson, 1992;Bologna & Camp, 1997;Mayhew, Acton, Yauk, & Hopkins, 2001;Tappen, Williams, Fishman, & Touhy, 1999) and five as low quality (Grewal, 1994;Lancioni et al, 2013Lancioni et al, , 2015Mangone et al, 1991;Yokoi, Haraguchi, Hashimoto, & Okamura, 2012).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The number of participants varied considerably across studies, with a median sample size of 11 (range 3-77). Nine studies were defined as high quality (Avondino & Antoine, 2016;Beach et al, 2015;Conde-Sala et al, 2013Magai et al, 1996, P€ oll€ anen & Hirsim€ aki, 2014Starkstein, Jorge, Mizrahi, & Robinson, 2006;Swall, Ebbeskog, Lundh, & Fagerberg, 2015), seven as moderate quality (Asplund, Jansson, & Norberg, 1995;Asplund, Norberg, Adolfsson, & Waxman, 1991;Biringer, Anderson, & Strubel, 1988;Biringer & Anderson, 1992;Bologna & Camp, 1997;Mayhew, Acton, Yauk, & Hopkins, 2001;Tappen, Williams, Fishman, & Touhy, 1999) and five as low quality (Grewal, 1994;Lancioni et al, 2013Lancioni et al, , 2015Mangone et al, 1991;Yokoi, Haraguchi, Hashimoto, & Okamura, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Overall, the existing literature highlights that environmental contexts play a significant role in facilitating or preventing the expression of awareness in severe AD. Several studies reported that various environmental stimuli effected the expression of lower level sensory awareness in severe AD patients, such as listening to music (Lancioni et al, 2013(Lancioni et al, , 2015 and sitting in a rocking-chair (Asplund et al, 1991). Environmental cues, including name tags and labels, also appeared to influence self-recognition in individuals who could not independently demonstrate this ability (Bologna & Camp, 1997).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations